TRIAL WITHIN A REASONABLE TIME - Remedies safeguarding the right to trial within a reasonable time - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The paper offers analysis of legislation of the Republic of Serbia relating to trial within a reasonable time. The author draws a conclusion that the trial within reasonable time is a right granted to the parties to the proceedings, guaranteed by special legal remedies, decided upon by a higher court. The higher court does not decide the merits of the case, rather it only points to the reasons that caused the rights of the parties to be violated and instructs the judge to take actions, within a set time, that are directed at speeding up the proceedings. Also, the new Law on Protection of the Right to a Trial within a Reasonable Time of the Republic of Serbia provides for compensation of damages to a party to the proceedings that suffered damages as a result of unreasonable delay in the proceedings. In order for such damages, borne by the Republic of Serbia, to be awarded, it is necessary that such delay in the proceedings to be caused by the court, not by the parties. Further, the paper raises issues concerning mutatis mutandis application of the Law on Civil Procedure and the Law on Non-Contentious Proceedings. The author supports mutatis mutandis application of the rules governing civil procedure to compensation of damages and mutatis mutandis application of the rules governing non-contentious proceedings to requests for speeding up the proceedings. This is in contrast to the present wording of the Law that envisages mutatis mutandis application of the Law on Non-Contentious Proceedings in all cases. The author finds reasons for such position in the contentious nature of the request for speeding up the trial and in adversarial nature of the claim to damages.